What Does a Quality Education Look Like in Rural Schools? - Guenther, John; Fuqua, Melyssa (Australian and International Journal of Rural Education, 2024)
This issue of the Australian and International Journal of Rural Education features articles that describe and critically analyse rural education, the common thread being 'What Does a Quality Education Look Like in Rural Schools?'. The education settings discussed include Australia, Czechia, Iraq, South Africa, Sweden, Tanzania, and the United States. The studies presented reflect the huge diversity of rural schooling and the many factors that work to support quality education. What does quality rural education look like? It looks like teachers who have a strong connection to place, with strategies for teaching that connect with students from the place. It looks like teachers who are flexible and open to learning. It looks like a supportive system. It looks attractive to parents. It looks like contextualised learning. It looks like parents and communities engaged in their children's learning at school. It is potentially transformative. It looks like a workforce that has good access to professional learning options. It looks like good governance, with local Elders and community leaders involved and driving a vision for education. It looks like strong peer relationships, and a culturally safe learning environment. It does not necessarily look like the narrowly defined metrics that are often used to define success or the deficits that are too often described in association with rural education.